Social dynamics and stability of human society - Semenok, Dmitrii (Frontiers in Physics, 2025)
Sociophysics involves the use of physical models to describe human society. This makes it possible to simplify the construction of social models and use concepts, equations, and consequences from them, already well-known in physics. In this work, a system of equations is proposed that describes the dynamics of human society in an N-dimensional social space, introduced on the basis of a widely used survey method. The proposed system of equations links such parameters as social density, velocity of social flows, gradient of social pressure, and social potential, as well as their derivatives with respect to social coordinates and time. The constructed system of equations is similar to multidimensional Navier-Stokes equations for a fluid with variable density, viscosity, and non-stationary temperature distribution. This excludes the possibility of an analytical solution of the system in the general case and leaves a door open only for numerical simulations with the prediction of future behavior at short time intervals in a common way in meteorology. Proposed simple model of social dynamics is based on the assumptions of metricity and continuity of the N-dimensional social space, the presence of potential forces of paired interaction of social particles both among themselves and with the field of things, which is the main factor of indirect attraction of people to each other. The model is built in a sequence similar to the structure of classical fluid mechanics and thermodynamics. The purpose of this article is to point out the main qualitative results to which this model leads.